Optic Nerve Sheath Diameter Ultrasound: A Non-Invasive Approach to Evaluate Increased Intracranial Pressure in Critically Ill Pediatric Patients - Giulia Cannata; Stefano Pezzato; Susanna Esposito; Andrea Moscatelli (Diagnostics, 2022)
Early diagnosis of increased intracranial pressure (ICP) is crucial for prompt diagnosis and treatment of intracranial hypertension in critically ill pediatric patients, preventing secondary brain damage and mortality. Although the placement of an external ventricular drain coupled to an external fluid-filled transducer remains the gold standard for continuous ICP monitoring, other non-invasive approaches are constantly being improved and can provide reliable estimates. The use of point-of-care ultrasound (POCUS) for the assessment of ICP has recently become widespread in pediatric emergency and critical care settings, representing a valuable extension of the physical examination. The aim of this manuscript is to review and discuss the basic principles of ultra-sound measurement of the optic nerve sheath diameter (ONSD) and summarize current evidence on its diagnostic value in pediatric patients with ICP. There is increasing evidence that POCUS measurement of the ONSD correlates with ICP, thus appearing as a useful extension of the physical examination in pediatrics, especially in emergency medicine and critical care settings for the initial non-invasive assessment of patients with suspected raised ICP. Its role could be of value even to assess the response to therapy and in the follow-up of patients with diagnosed intracranial hypertension if invasive ICP monitoring is not available. Further studies on more homogeneous and extensive study populations should be performed to establish ONSD reference ranges in the different pediatric ages and to define cut-off values in predicting elevated ICP compared to invasive ICP measurement.